2018
DOI: 10.1096/fj.201800172r
|View full text |Cite
|
Sign up to set email alerts
|

Two intrauterine programming mechanisms of adult hypercholesterolemia induced by prenatal nicotine exposure in male offspring rats

Abstract: Epidemiologic studies showed that low birth weight is associated with high cholesterol and an increased risk of cardiovascular diseases in adulthood. This study aimed to elucidate the intrauterine programming mechanisms of adult hypercholesterolemia. The results showed that prenatal nicotine exposure (PNE) caused intrauterine growth retardation and hypercholesterolemia in male adult offspring rats. Hepatic cholesterol synthesis and output were deceased in utero but increased in adults; hepatic reverse choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…A series of our previous studies confirmed that PNE enhances maternal serum GC level, inhibits GC inactivation in placenta barrier, and subsequently raises maternal‐originated GC concentration in foetal blood, and consequently inhibits development of neuroendocrine metabolic function. Our recent study found that expression of SR‐B1 and LDLR in PNE foetal liver was significantly lower than that in the control, and we also detected low histone acetylation at promoter regions of these two genes, which indicated that epigenetic modification was probably involved in PNE‐induced programming alteration of cholesterol reverse transportation genes. Intrauterine programming of neuroendocrine metabolism results in glucose and lipid metabolic disorder, which may continue after birth and increase progeny susceptibility to MS …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A series of our previous studies confirmed that PNE enhances maternal serum GC level, inhibits GC inactivation in placenta barrier, and subsequently raises maternal‐originated GC concentration in foetal blood, and consequently inhibits development of neuroendocrine metabolic function. Our recent study found that expression of SR‐B1 and LDLR in PNE foetal liver was significantly lower than that in the control, and we also detected low histone acetylation at promoter regions of these two genes, which indicated that epigenetic modification was probably involved in PNE‐induced programming alteration of cholesterol reverse transportation genes. Intrauterine programming of neuroendocrine metabolism results in glucose and lipid metabolic disorder, which may continue after birth and increase progeny susceptibility to MS …”
Section: Discussionmentioning
confidence: 52%
“…Our recent work found that serum corticosterone of PNE pup increased significantly in uterine, but decreased in adulthood. In contrast, IGF1 level increased after birth, accompanied by an enhanced mRNA expression of HMGCR and ApoB . Incubation with IGF1 also increased ApoB expression in HepG2 cells …”
Section: Discussionmentioning
confidence: 85%
“…Reproductive function inhibition of male rats under long-term chronic stress is associated with increased serum corticosterone levels [ 60 , 61 ]. Our previous study found that prenatal exposure to nicotine, ethanol, or caffeine induced multi-organ dysplasia in offspring mainly attributed to an activated maternal HPA axis [ 62 , 63 , 64 ]. In this study, we found that the body weight and growth rate of paternal rats in the PME group were gradually decreased in a time-dependent manner but the activity of the HPA axis and the function of adrenal steroid synthesis were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Pumps were loaded with nicotine (Wako Pure Chemical Industries, Ltd., Kyoto, Japan), formulated in saline, at a concentration designed to deliver the drug at an initial dose rate of 3 mg nicotine/kg bodyweight/day for 28 days (starting from one week before the projected mating day through the day of delivery). Several previous papers have reported administration of nicotine to pregnant rat dams at doses ranging from 1 to 5 mg/kg bodyweight/day (19)(20)(21). For the present study, we selected a nicotine dose level of 3 mg nicotine/kg bodyweight/day per pregnant rat dams based on preliminary experiments at various dose level; notably, these data (not shown) are not detected a difference in mean food intake, and gestational age between dams maintained on vehicle compared to those maintained on nicotine at 3 mg nicotine/kg bodyweight/day.…”
Section: Animalsmentioning
confidence: 99%